PROFIL PASIEN DEMAM TIFOID DAN PENGOBATAN DI BAGIAN PENYAKIT DALAM RUMAH SAKIT PIRNGADI MEDAN TAHUN 2016 - MUHAMMAD FADHIL; NELLI MURLINA; YENITA .; SHAHRUL RAHMAN (JURNAL ILMIAH SIMANTEK, 2021)
The type of research used in this study is a descriptive study with a cross sectional design to determine the profile andtreatment of typhoid fever patients in the internal medicine department of Pirngadi hospital Medan in 2016 through medicalrecord data. Based on the genitalia, male as many as 33 samples and females as many as 49 samples. Based on the age,teenager as many as 6 samples, young adults as many as 47 samples, adults as many as 27 samples, elderly as many as 2samples. Based on the work, students as many as 6 samples, college student as many as 21 samples, goverment employeeas many as 7 samples, entrepeneur as many as 15 samples, private employees as many as 10 samples, retirees as manyas 4 samples, farmers as much as 2 samples, housewife as many as 14 samples, unemploymeent 3 people. Based on thetreatment of antibiotics, cifrofloxacin as many as 25 samples, levofloxacin as many as 9 samples, ceftriaxone as many as 37samples, cefixime as many as 7 samples, cefadroxyl as many as 1 sample, cefotaxime 1 sample, cotrimoxazole 1 sample.Based on antipyretic treatment, as many as 82 samples of paracetamol.